The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/cid.12161
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Characteristics around Healing Abutments of Different Geometries: New Methodological Technique under Circularly Polarized Light

Abstract: Abutment geometry influences the orientation of collagen fibers; therefore, an abutment with a profile wider than the implant platform favors oblique and perpendicular orientation of collagen fibers and greater connective tissue thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…In this connective tissue region, the results obtained in the present study were similar to the ones reported by Delgado‐Ruiz et al. () in the group with wider abutments in terms of collagen fiber orientation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this connective tissue region, the results obtained in the present study were similar to the ones reported by Delgado‐Ruiz et al. () in the group with wider abutments in terms of collagen fiber orientation.…”
Section: Discussionsupporting
confidence: 92%
“…Delgado‐Ruiz et al. () studied the orientation of collagen fibers surrounding abutments with different geometries at different regions of the connective tissue area. In that study, it was observed that abutment geometry influenced the orientation of collagen fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, as in a study published by Delgado‐Ruiz et al. (), to study connective tissue fiber orientation, the long axis of the implant was used as a reference, starting in the coronal zone and ending in the basal zone. Collagen fiber density was observed to be higher in the plasma group in the basal, medial, and coronal area compared to the control group with a statistical difference in the internal area ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This produced a clear image that permitted the accurate observation of collagen in biological tissues (Delgado‐Ruiz et al. ).…”
Section: Methodsmentioning
confidence: 99%